Effect of PAC particle layer on the performance of gravity-driven membrane filtration (GDM) system during rainwater treatment. Issue 1 (25th October 2017) - Ding, An; Wang, Jinlong; Lin, Dachao; Cheng, Xiaoxiang; Wang, Hui; Bai, Langming; Ren, Nanqi; Li, Guibai; Liang, Heng
Abstract : The gravity-driven membrane filtration (GDM) process is very suitable for decentralized drinking water or rainwater treatment due to low maintenance (no backwashing, physical flushing and chemical cleaning) and low energy consumption. Abstract : The gravity-driven membrane filtration (GDM) process is very suitable for decentralized drinking water or rainwater treatment due to low maintenance (no backwashing, physical flushing and chemical cleaning) and low energy consumption. However, the ultrafiltration process alone seldom satisfies the standard of organics removal. To meet the purpose of water reuse, we applied a powdered activate carbon (PAC) layer and sand layer on the membrane surface of a GDM system to improve the quality of the effluent in this study. In addition, the flux development and fouling layer properties were also systematically investigated. Results show that the presence of a PAC layer enhanced the organics removal by nearly 20%, including the fluorescent organics (such as aromatic proteins, tryptophan proteins and humics) removal. However, the sand layer assisted system did not show any improvement, as observed when compared with the control. With regard to the permeate flux development tendency, the flux could be kept stable in the PAC/GDM system (3.0 L m −2 h −1 ) and control system (4.5 L m −1 h −1 ), whereas the flux of the sand/GDM system did not stabilize with the final value of 2.3 L m −2 h −1 on day 55. The reason for the lower stable flux in PAC/GDM system was that PAC acted as a bio-carrier and that a large amount of biomass with higher EPS contents (proteins and polysaccharides) developed on the membrane. The main explanation for the unstable flux in the sand/GDM system was the low porosity of the bio-fouling layer, which significantly increased the hydraulically reversible and cake layer resistances. However, the permeate flux could be restored easily in these systems by simple flushing because hydraulically reversible resistance accounted for large proportions (>90%) of the total filtration resistance.